The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4236/abb.2010.11006
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte modulated enhanced rice leaf catalase activity under salt-stress

Abstract: Change in catalase activity was examined in leaves of rice plant exposed to salinity. Depending on the method of preparation of crude protein extract from leaf and the constituents of the assay medium, a significant difference in enzyme activity was recorded. Inclusion of sorbitol or mannitol or sucrose in the extraction and enzyme assay medium enhanced the enzyme activity in salt-stressed samples by nearly 1.5-1.8 fold, compared to the activity found in unstressed plants, which otherwise showed a 50% declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…As expected Sahu et al (2010) have shown a declined rice leaf catalase activity under elevated salt-treatment, however, surprisingly, supplementation of sucrose significantly rescues salt mediated decay in catalase activity. The investigation also evidenced that catalase in rice leaf interacts with sucrose under in vivo condition and renders a protective role in maintaining high enzymatic activity thus acting as the principal enzymatic source for scavenging the stress induced production of H 2 O 2 (Sahu et al, 2010).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…As expected Sahu et al (2010) have shown a declined rice leaf catalase activity under elevated salt-treatment, however, surprisingly, supplementation of sucrose significantly rescues salt mediated decay in catalase activity. The investigation also evidenced that catalase in rice leaf interacts with sucrose under in vivo condition and renders a protective role in maintaining high enzymatic activity thus acting as the principal enzymatic source for scavenging the stress induced production of H 2 O 2 (Sahu et al, 2010).…”
Section: Introductionsupporting
confidence: 83%
“…Plants treated with different concentrations of sucrose under salt stress condition induces metabolic pathways and induced systemic responses that reprogrammed the whole/partial catabolic and metabolic cascade related to salt tolerance and signalling (Kumar et al, 2013;Sahu et al, 2010). It was found that plants treated with sucrose activated stress related cascade and caused manifold increase in the activation of catalase activities (Fig.…”
Section: Estimation Of Catalase Activitymentioning
confidence: 94%
“…In situ detection of hydrogen peroxide (H 2 O 2 ) was performed by staining the tissue with DAB (Sigma-Aldrich) as suggested (Bindschedler et al 2006). Steady-state levels of H 2 O 2 in leaves were determined following FOX-1 method (Sahu et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress is a result of the imbalance between reactive oxygen species (ROS), nitrogen (ERN) and the antioxidant defense system present in the body (Sahu et al 2010). When such a balance tends towards an excessive production of these compounds or a deficiency of the antioxidant systems, the oxidative stress condition arises, which is harmful to the cellular components and to the individuals as a whole (Carocho and Ferreira 2013).…”
Section: Introductionmentioning
confidence: 99%